Arthropod-Borne Viruses The Outbreak Edition - Kading, Rebekah C.; Brault, Aaron C; Beckham, J. David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Arthropod-borne viruses affect billions of people around the world and comprise a significant proportion of emerging human pathogens. This Special Issue provides a global perspective on emerging arboviruses in endemic regions, as well as areas of introduction. Articles span entomological, clinical, and epidemiological aspects of West Nile virus, Rift Valley fever virus, Japanese encephalitis virus, Zika virus, chikungunya virus, Crimean Congo hemorrhagic fever virus, tick-borne encephalitis virus, and Venezuelan equine encephalitis virus.